The Relevance and Viability of Subconscious Goals in the Workplace - Latham, Gary P.; Stajkovic, Alexander D.; Locke, Edwin A. (Journal of Management, 2010)
This article examines the relevance and viability of pursuing empirical research on subconscious goals and applying the findings in the workplace. Five topics are addressed: First, reasons why management scholars have eschewed the study of the subconscious are given. Second, a brief overview of social psychology experiments on subconscious goals is provided. Critical issues that have yet to be addressed in these experiments are identified and discussed. Third, organizational psychology experiments on subconscious goals that have attempted to overcome several of these shortcomings and provide new findings are described. Fourth, research avenues that have yet to be explored are suggested. Finally, the implications of this stream for management practice are discussed.